A history of biological control in Canadian forests, 1882–2014. (14th January 2016) - MacQuarrie, Chris J.K.; Lyons, D.B.; Lukas Seehausen, M.; Smith, Sandy M.
Abstract: Biological control has been an important tactic in the management of Canadian forests for over a century, but one that has had varied success. Here, we review the history of biological control programmes using vertebrate and invertebrate parasitoids and predators against insects in Canadian forests. Since roughly 1882, 41 insect species have been the target of biological control, with approximately equal numbers of both native and non-native species targeted. A total of 161 species of biological control agents have been released in Canadian forests, spanning most major orders of insects, as well as mites and mammals. Biological control has resulted in the successful suppression of nine pest species, and aided in the control of an additional six species. In this review, we outline the chronological history of major projects across Canadian forests, focussing on those that have had significant influence for the development of biological control. The historical data clearly illustrate a rise and fall in the use of biological control as a tactic for managing forest pests, from its dominance in the 1940s and 1950s to its current low level. The strategic implementation of these biological control programmes, their degree of success, and the challenges faced are discussed, along with the discipline's shifting relationship to basic science and the environmental viewpoints surrounding its use.